TOMATO SEED INVIGORATION WITH CYTOKININS - A. Nawaz; M. Amjad; S. M. Khan; I. Afzal; T. Ahmed; Q. Iqbal; J. Iqbal (Journal of Animal and Plant Sciences, 2013)
The study was carried out to investigate the effects of hormonal priming on germination and seedling growth of tomato seeds. Priming was done by exposing seeds of two tomato cultivars ‘Nagina’ and ‘Pakit’ to aerated solutions of (Cytokinins) 10, 50 and 100 ppm BAP and kinetin for 24 h. The performance of primed and non primed seeds was evaluated during germination and emergence tests under controlled conditions by using completely randomized design with three replications. Seed priming with 10 ppm kinetin increased final germination percentage, germination index, shoot length and seedling fresh weight of both tomato cultivars as compared to all other presowing seed treatments including control. Seeds of both tomato cultivars primed with 10 ppm kinetin for 24 h significantly reduced the time taken to 50% emergence and mean emergence, increased final seedling emergence percentage and seedling growth. Results indicated that cytokinins priming with varying concentrations of BAP and kinetin improved germination potential and seedling establishment of both cultivars. Maximum improvement was recorded in seeds primed with 10 ppm kinetin. The better performance of primed seeds may be due to lower electrical conductivity (EC) of seed leachates.
Keywords: Seed dormancy; cytokinins; electrical conductivity